Penyuluhan Penggunaan Listrik yang Efisien dan Aman di Dusun Palintang, Cipanjalu, Cilengkrang, Kabupaten Bandung - Heri Andrianto; Aikho Pasodung (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
One of the prevalent issues in rural communities is the low awareness of efficient and safe use of electricity and electrical appliances, often resulting in hazards such as short circuits, electric shocks, and residential fires, particularly among housewives as the primary users. In response, an educational outreach was conducted on March 18, 2025, as part of the Community Service Program (KKNT) in Palintang Hamlet, Cipanjalu Village. The objective was to provide education and raise awareness about efficient and safe electricity use. Sixteen housewives participated, using the Participatory Action Research (PAR) method with a pre-test and post-test design. The content included electrical safety tips, demonstrations of proper cable installation, and best practices for using electrical appliances. To assess effectiveness, participants completed pre- and post-tests. Results indicated a significant knowledge improvement, with average scores increasing from 73 to 98. This demonstrates the training’s effectiveness in enhancing awareness and understanding of safe electricity use. Participants showed high engagement and expressed intentions to apply the knowledge in their households. This initiative highlights the potential of practical electrical education in rural settings to improve community safety.